Combined oral contraceptives in the prevention of recurrence of typical endometrial hyperplasia of endometrium - A L Tikhomirov (IP Berlin A.V., 2018)
Changes in consideration of etiology and pathogenesis of hyperplastic endometrial processes allowed to claim that their preventive maintenance using modern hormonal contraceptives may significantly reduce the frequency and volume surgical treatment. The main protections are ovulation suppression COC mechanism and suppression folliculogenesis, i.e. monthly do not always adequately cyclic processes in endometrium.